Have marine natural product drug discovery efforts been productive and how can we improve their efficiency? - Pereira, Florbela (2019)
F Pereira is supported by the Fundacao para a Ciencia e Tecnologia (FCT), Portugal via grant SFRH/BPD/108237/2015 and grant UID/QUI/50006/2019 (provided to the Associate Laboratory for Green Chemistry-LAQV)